Characterization and Genomic Analysis of a New Phage Infecting Helicobacter pylori - Ferreira, Rute (2022)
Helicobacter pylori, a significant human gastric pathogen, has been demonstrating increased antibiotic resistance, causing difficulties in infection treatment. It is therefore important to develop alternatives or complementary approaches to antibiotics to tackle H. pylori infections, and (bacterio) phages have proven to be effective antibacterial agents. In this work, prophage isolation was attempted using H. pylori strains and UV radiation. One phage was isolated and further characterized to assess potential phage-inspired therapeutic alternatives to H. pylori infections. HPy1R is a new podovirus prophage with a genome length of 31,162 bp, 37.1% GC, encoding 36 predicted proteins, of which 17 were identified as structural. Phage particles remained stable at 37 C, from pH 3 to 11, for 24 h in standard assays. Moreover, when submitted to an in vitro gastric digestion model, only a small decrease was observed in the gastric phase, suggesting that it is adapted to the gastric tract environment. Together with its other characteristics, its capability to suppress H. pylori population levels for up to 24 h post-infection at multiplicities of infection of 0.01, 0.1, and 1 suggests that this newly isolated phage is a potential candidate for phage therapy in the absence of strictly lytic phages.